Answer:
(2,1)
Explanation:
Well first we single out y or x in one of the equations,
we’ll use 2x + y = 5 and single out y.
2x + y = 5
-2x to both sides
y = -2x + 5
So we can plug in -2x + 5 into y in 2x - 2y = 2.
2x - 2(-2x + 5) = 2
2x + 4x - 10 = 2
combine like terms,
6x - 10 = 2
Communicarice property
+10 to both sides
6x = 12
divide 6 to both sides
x = 2
If x is 2 we can plug 2 in for x in 2x + y = 5.
2(2) + y = 5
4 + y = 5
-4 to both sides
y = 1
(2,1)
Thus,
the solution is (2,1).
Hope this helps :)